ANALISIS USAHATANI TALAS SATOIMO (Colocasia esculenta var. antiqourum) (Studi Kasus : di Desa Suka Sari Kecamatan Kabawetan Kabupaten Kepahiang) - Dhanty Dwika Amelia; Yossie Yumiati (UNIVED Press, Universitas Dehasen Bengkulu, 2016)
This study aimed to analyze the system of processing, large production and productivity, substancial net income, and economic analysis review of satoimo taro farm commodities in Sukasari village Kabawetan subdistrict Kepahiang District Bengkulu Province. The research method involves taking sample by using census method, data collection taken from secondary and primary data, data analysis using the formula π = TR-TC (net income), R / C Ratio to measure the feasibility of farming economically. The system of processing satoimo taro farming carried out in the area of research in the form of land preparation, planting, fertilizing, and landfill that still relatively modest yet as recommended by the literature (according to Hodijah, 2009). The average production sataimo taro farm amounted to 3,265 kg satoimo and productivity of 14.446 kg/ha is still low compared to the literature (SEAMEO BIOTROP Research Bogor West Java). Total net income satoimo taro farm during one growing season is Rp127.319.464, -. Analysis of R/C ratio is 2.07 satoimo taro farm therefore the farming is economically feasible to be developed (R / C ≥ 1). Keywords: Satoimo Taro, Land management, Production and Productivity, Net Income, analysis of R / C ratio